An environmentally friendly and productive process for bioethanol production from potato waste. Issue 1 (December 2016) - Wang, Fangzhong; Jiang, Yi; Guo, Wei; Niu, Kangle; Zhang, Ruiqing; Hou, Shaoli; Wang, Mingyu; Yi, Yong; Zhu, Changxiong; Jia, Chunjiang; Fang, Xu
Abstract Background China is the largest sweet potato producer and exporter in the world. Sweet potato residues (SPRs) separated after extracting starch account for more than 10 % of the total dry matter of sweet potatoes. In China, more than 2 million tons of SPRs cannot be utilized, and the unutilized SPRs are perishable and result in environmental pollution. Thus, an environmentally friendly and highly efficient process for bioethanol production from SPRs should be developed. Results The swelling behaviour of cellulose causes high-gravity sweet potato residues to be recalcitrant to enzymatic hydrolysis. Cellulase plays a major role in viscosity reduction and glucose production. In contrast, pectinase has a minor role in viscosity reduction but acts as a "helper protein" to assist cellulase in liberating glucose, especially at low cellulase activity levels. In total, 153.46 and 168.13 g/L glucose were produced from high-gravity SPRs with cellulase and a mixture of cellulase and pectinase, respectively. These hydrolysates were fermented to form 73.37 and 79.00 g/L ethanol, respectively. Each kilogram of dry SPR was converted to form 209.62 and 225.71 g of ethanol, respectively. Conclusion The processes described in this study have an enormous potential for industrial production of bioethanol because they are environmentally friendly, highly productive, economic with low cost, and can be easily manipulated.